KETERAMPILAN MEMBACA KRITIS PADA MAHASISWA JURUSAN PERBANKAN SYARIAH SEMESTER IV FAKULTAS SYARIAH DAN HUKUM, UIN SYARIF HIDAYATULLAH JAKARTA - Dona Aji Karunia Putra (Dialektika: Jurnal Bahasa, Sastra, dan Pendidikan Bahasa dan Sastra Indonesia, 2015)
The issue of the lack tradition of reading among students needs attention and solution. Students need to be inspired, motivated, and facilitated so diligent and intense reading. For the progress of the study, reading is the basic skills are constantly required by the student. In the context of a student in college, an important reading skill by a student is critical reading skills. Critical reading skills involve aspects of critical thinking. Students trying to explore what were stated in the reading material and trying to explore the meaning. A critical reading activity not just memorize, but students with critical reading skills is possible does not accept what is presented, even college students understand the concept of what she or he had. Basically, when someone doing critical reading activity, he did it with thoughtful, attentive, insightful, analytical, evaluative, and instead want to find mistakes the author. Based on the facts and phenomena, critical reading skills so necessary for a college student. This study aims to describe the level of critical reading skills in college students majoring in Islamic Banking IV semester academic year 2012/2013. The research was conducted using a quantitative approach. This research uses the descriptive method. The population in this research is the whole Islamic Banking Majors semester IV amounted to 125. This research sample taken using proportional random sampling. Based on the model of random sample research, determined that Islamic Banking Majors semester IV class B and D of 59 people. The results showed that in general a student majoring in Islamic Banking Semester IV is quite skilled in the critical reading of a text. It is reflected in the statistical data indicating that the average value of the total of the skills of critical reading of a text on Islamic Banking majors semester IV is at number 77,35 and is skilled enough to qualify. Specifically, the percentage of the skill level of every aspect of critical reading on Islamic Banking Majors Semester IV can be outlined as follows, (1) aspects of skills to determine the facts in the text represents 22.5% of the total critical reading skills, (2) aspects of skills to determine the opinion in the text represents 22.2% of the total critical reading skills, (3) aspects of skills conclude text content representing 20.3% of the total critical reading skills, (4) aspects of skills analyze the use of the language within the text represent 15.7% of the total critical reading skills, (5) aspects of skills opined against text content represent 19,3% of the total critical reading skills.